The frequency of diastolic dysfunction in patients with sarcoidosis and it’s relationship with HLA DRB1* alleles - Ozyilmaz, Ezgi; Akilli, Rabia; Berk, Ilayda; Deniz, Ali; Goruroglu Ozturk, Ozlem; Baydar, Oya; Saygideger, Yasemin; Seydaoglu, Gulsah; Erken, Eren (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: Impaired systolic function is common in sarcoidosis however the frequency of diastolic dysfunction (DD) and it’s possible genetic basis has not been fully elucidated yet. The aim of this study is to evaluate the frequency of left ventricular DD(LVDD) and right ventricular DD(RVDD) and it’s possible relationship between Human Leukocyte Antigen(HLA)-DRB1* alleles in patients with sarcoidosis. Methods: Seventy seven patients (51 females, mean age 41.1±8.2yrs) without known sarcoid related or any other structured heart disease and 77 healthy controls with a similar age and gender (38.7±7.8yrs,51 females) were included in the case control study. DD was diagnosed with echocardiography. RVDD was defined as early(E)/late(A) ratio<1 or >2 on tricuspit valve. LVDD was defined as E/A ratio<1 or >2 on mitral valve, with isovolumetric relaxation time(IVRT)>90 miliseconds(msn) or deceleration rate of early diastolic flow(Edec)>220msn respectively. All patients were HLAtyped with the Sequence Specific Oligonucleotide Probe(SSOP) method. Results: The frequencies of LVDDs and RVDDs were significantly higher in sarcoidosis patients than the controls (26.0% vs. 2.6% for LVDD; and 42.9% vs. 18.2% for RVDD)(p<0.05). No significant difference was found in patients according to the presence of RVDD and LVDD in terms of age, gender or respiratory function test parameters. Although the frequency of HLA DRB1* alleles were comparable among patients with RVDD, HLA DRB1*14 alleles were more frequent in patients with LVDD. Conclusions: Biventricular DD is common in patients with sarcoidosis without manifest cardiac involvement. HLA DRB1*14 allele seems to be related with LVDD in this study population.